2018
DOI: 10.31248/jasvm2018.103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Turmeric rhizome (Curcuma longa) powder and coconut oil mixture on growth performance, haematological and biochemical parameters of noiler birds

Abstract: This study was conducted to assess the effect of Curcuma longa on growth performance, haematological and biochemical parameters of noiler birds. A total of sixty-four (64) noiler birds of both sexes with an average weight of 1974±0.03 g were randomized into four treatment groups. Each treatment group comprised of eight birds per replicate and was replicated twice. Treatment 1 (control), treatment 2 (turmeric at 10 g/kg of feed), treatment 3 (turmeric at 20 g/kg of feed) and treatment 4 (selcon forte at 0.5 g/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The decreased serum creatinine levels in the groups supplemented with essential oils may be attributed to better protein metabolism and thus a reduction in activity of muscle wasting. Oyebanji et al (2018) found a significant reduction in serum bilirubin concentration in birds supplemented with turmeric powder. In present study, decrease in serum bilirubin concentrations may be because of antioxidant properties of essential oils.…”
Section: Serum Biochemical Parametersmentioning
confidence: 88%
“…The decreased serum creatinine levels in the groups supplemented with essential oils may be attributed to better protein metabolism and thus a reduction in activity of muscle wasting. Oyebanji et al (2018) found a significant reduction in serum bilirubin concentration in birds supplemented with turmeric powder. In present study, decrease in serum bilirubin concentrations may be because of antioxidant properties of essential oils.…”
Section: Serum Biochemical Parametersmentioning
confidence: 88%
“…as a solvent according to the method described by AOAC [2]. At the end of the extraction, the extraction solvent was evaporated in a rotary evaporator [37].…”
Section: Melon Seed Oilmentioning
confidence: 99%
“…Noiler chicken is a dual purpose breed of chicken developed by Amo Farm Sieberer Hatchery Limited for small holders to address the challenges of food insecurity and financial dependency among the rural populace, especially women. Noiler was bred to survive on low quality feedstuffs to provide good quality meat and egg [37].…”
Section: Introductionmentioning
confidence: 99%
“…Noiler is a dual-purpose chicken producing excellent meat and eggs for smallholders to combat food insecurity and improve financial dependency (Oyebanji et al, 2018). Noiler is a crossbreed between a broiler and a local chicken (Adeleke et al, 2010).…”
Section: Introductionmentioning
confidence: 99%